2020
DOI: 10.14232/abs.2019.2.91-101
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological, anatomical and molecular study of Hedera species (Araliaceae) in Iran

Abstract: Hedera, with 12 extant species, is a genus of evergreen climbers native to Europe, north Africa, and south Asia. In this study, the micromorphological, anatomical structure and molecular evidences of 11 populations from two species of Hedera (H. helix and H. pastuchovii) have been considered to evaluate the relationships in Hedera. In total, seven quantitative and qualitative characters of pollen were selected and measured. Based on this study, the anticlinal wall and surface sculpturing of seed support for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As Hart and Henwood [2006] and Wen [2011] demonstrated, the indumentum in the araliaceans often comprises simple or multicellular stellate trichomes. As suggested by Amini et al [2019] and Lestari and Elya [2019], the presence of secretory ducts, calcium oxalate crystals, and non-glandular trichomes has great diagnostic importance in Hedera spp. and the family Araliaceae.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As Hart and Henwood [2006] and Wen [2011] demonstrated, the indumentum in the araliaceans often comprises simple or multicellular stellate trichomes. As suggested by Amini et al [2019] and Lestari and Elya [2019], the presence of secretory ducts, calcium oxalate crystals, and non-glandular trichomes has great diagnostic importance in Hedera spp. and the family Araliaceae.…”
Section: Discussionmentioning
confidence: 92%
“…It supports the data by Săvulescu and Luchian [2009], who showed that these cells had thin walls, prominent nuclei, and dense cytoplasm. As shown by Amini et al [2019], H. helix petioles have 9 to 12 secretory ducts, whereas their number in H. pastuchovii petioles is lower, i.e. from 6 to 8.…”
Section: Discussionmentioning
confidence: 92%
“…Clarke, and Heteropanax Seem. ; Jebb, 1998 ; Shang et al, 2000 ; Jamir and Pandey, 2003 ; Heriyanto and Sawitri, 2007 ; Prabhu et al, 2010 ; Tagane et al, 2017 ; Jiménez‐Montoya and Idárraga‐Piedrahíta, 2018 ; Ong, 2018 ; Amini et al, 2020 ). Because most of these localities lacked longitude and latitude coordinates, coordinates were determined using GeoLocate Web Application (Rios and Bart, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…and Sche era pueckleri are the modern names of Sciadophyllum pulchrum leaves. Amini et al(2019) studied the micromorphology of Hedera species in Iran. Lestari and Elya (2019) made macroscopic studies of Polyscias guilfoylei leaves.…”
Section: Introductionmentioning
confidence: 99%